Digital Multisided Platforms and Women’s Health: An Empirical Analysis of Peer-to-Peer Lending and Abortion Rates - Ozer, Gorkem Turgut; Greenwood, Brad N.; Gopal, Anandasivam (Information Systems Research, 2023)
Access to short-term capital remains a pressing problem for many people, especially those facing medical emergencies or needing immediate care. Peer-to-peer lending platforms have the ability to resolve these capital constraints by providing access to small to medium sums of money in an environment that is private and protective of personal information. In this study, we consider how the introduction of P2P lending platforms, and the resulting access to capital, influences local abortion rates, a medical procedure characterized by significant financial barriers and social stigma. We find that the entry of the P2P platform LendingClub is associated with an increase in the rate at which women choose to not carry to term. We argue that the availability of capital through these platforms, when combined with privacy protections, is able to reduce the financial barriers women face when accessing abortion services. This observed effect is stronger in more religious areas and areas with lower levels of education, indicating that social frictions and stigma may be higher in these areas, and also showing where providing an additional channel for funding is more influential.